A situação de Portugal na Europa no final do século XIX e início do século XX : a Geração de 70 - Natário, Celeste (2008)
The article presents the philosophical thought by the members of The 70s Generation. They were philosophers from different movements that tried to understand the meaning of the crisis in Portugal at that time. These men had the situation in Europe as their background and intended to establish in that country a moral and political revolution they wished to see spread over Europe.